The others [videorecording] - Cuerda, Joes Luis, production; Park, Sunmin, production; Amenabar, Alejandro, direction; Bovaire, Fernando ([S.l] : Cruise-Wagner/Sogecine/ Las productions del Escorpion, 2001)
The Island of Jersey, 1945. The Second World War is over but grace's husband has not returned from the front. Alone in a remote victorian mansion, she brings up her children within the menacing constraints of her strict religious principles. Her young daughter and son also suffer from a strange illness: they cannot be exposed to direct daylight. The house must always be kept in semidarkness. One foggy morning, three new servant turn up and strange things begin to happen. Grace begins to hear strange noises coming from upstairs, her husband suddenly returns from the front...
Sound, Ricardo Steinberg ; music, Alejandro Amenabar ; director of photography, Javier Aguirresarobe
Cast: Nicole Kidman (Grace)
Keywords: Horror films